Autoimmune Glial Fibrillary Acidic Protein Astrocytopathy Associated With Area Postrema Syndrome: A Case Report - Gao, Xin; Tang, Ying; Yang, Guo-Dong; Wei, Wu (Frontiers in Neurology, 2021)
Glial fibrillary acidic protein astrocytopathy is an immunotherapy-responsive autoimmune disease of the central nervous system with various clinical manifestations; among these, there are few reports about area postrema syndrome (APS). The authors present the case of a female patient admitted to the hospital with intractable nausea and vomiting as the predominant symptom. The patient's cerebrospinal fluid was tested by cell-based assays (CBA) and found positive for the presence of anti-glial fibrillary acidic protein (GFAP) antibody, in addition, serological testing showed elevated levels of thyroglobulin and thyroperoxidase-specific antibodies. Brain and cervical MRI showed abnormally high signal on the T2 sequence in the dorsal medulla oblongata and right pontine arm. Therefore, the patient was diagnosed with autoimmune GFAP astrocytopathy. The symptoms improved rapidly after treatment with corticosteroids, and no recurrence has been observed thus far. APS may be a relatively rare clinical manifestation of GFAP astrocytopathy. Importantly, such presentation is challenging to correctly diagnose without typical MRI imaging findings. However, the detection of antibodies in the cerebrospinal fluid or serum may be valuable. Systemic and neurological autoimmunity often coexist, comprehensive antibody screening should be conducted.